Genocide a comprehensive introduction - Jones, Adam (Routledge, Taylor & Francis Group, 2017)
Genocide: A Comprehensive Introduction is the most wide-ranging textbook on genocide yet published. The book is designed as a text for upper-undergraduate and graduate students, as well as a primer for non-specialists and general readers interested in learning about one of humanity's enduring blights.